Experimental Study of Geometrical Accuracy of Artec Leo 3D Scanner on Complex Object Scanning - Muhammad Khattami Al Saidhi; Rifelino Rifelino; Delima Yanti Sari; Febri Prasetya (Jurnal Vokasi Mekanika (VoMek), 2025)
This study aims to measure the geometrical accuracy of complex object scanning using the Artec Leo 3D scanner. The scanned object is a wheel rim, with eight combinations of parameters including variations in distance (50 cm and 100 cm), scanning angle (45° and 90°), and lighting conditions (indoor and outdoor). Deviations were measured from four reference points on the scanned model and compared to a reference model. The results show that the Indoor configuration with a scanning distance of 50 cm and a scanning angle of 90° gives the smallest deviation of 0.025 mm (0.01%), while the Outdoor configuration with a scanning distance of 50 cm and a scanning angle of 45° produces the largest deviation of -3.275 mm (-1.80%). The overall average deviation of all combinations is -0.63 mm or -0.36%, indicating that the Artec Leo can produce high accuracy if configured with the right parameters. The smallest deviation was obtained under indoor scanning conditions with a scanning distance of 50 cm and a scanning angle of 90°.